Satire on Stand Up Comedy “Messake Bangsaku” By Pandji Pragiwaksono - Ahmad Yusril Firdaus; Sulis Setiawati; Eko Yulianto (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The aim the research is to find out and analize satire of the stand up comedy “Mesakke Bangsaku” by Pandji Pragiwaksono. The writer use qualitative descriptive research in observing with content analysis technique. Resources of the research is video tape of stand up comedy “Mesakke Bangsaku” Pandji Pragiwaksono brings transcript into the writing process. Script product of transcription then, identify with use of satire’s theory. Based on analysis result, it find out satire with the highest percentage in the cynicism category which was as many as 39 of data or 38,23%. Another finding is, sarcasm category as many as 37 data (36,27%), ironic 4 data (3,92%), and antiphrase 1 data (0,98%).